Mechanistic Insight Into the Activation of the NLRP3 Inflammasome by Neisseria gonorrhoeae in Macrophages - Li, Lan-Hui; Lin, Jia-Sing; Chiu, Hsiao-Wen; Lin, Wen-Yu; Ju, Tz-Chuen; Chen, Fang-Hsin; Chernikov, Oleg V.; Liu, May-Lan; Chang, Jen-Che; Hsu, Chung-Hua; Chen, Ann; Ka, Shuk-Man; et al. (Frontiers in Immunology, 2019)
Gonorrhea is a type III legal communicable disease caused by Neisseria gonorrhoeae (NG), one of the most common sexually transmitted bacteria worldwide. NG infection can cause urethritis or systemic inflammation and may lead to infertility or other complications. The NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome is a protein complex composed of NLRP3, apoptosis-associated speck-like protein and caspase-1 and is an important part of the cellular machinery controlling the release of interleukin (IL)-1β and IL-18 and the pathogenesis of numerous infectious diseases. It has been reported that NG infection activates the NLRP3 inflammasome; however, the underlying mechanism remain unclear. In this report, the signaling pathways involved in the regulation of NG-mediated NLRP3 inflammasome activation in macrophages were studied. The results indicated that viable NG, but not heat-killed or freeze/thaw-killed NG, activated the NLRP3 inflammasome in macrophages through toll-like receptor 2, but not toll-like receptor 4. NG infection provided the priming signal to the NLRP3 inflammasome that induced the expression of NLRP3 and IL-1β precursor through the nuclear factor kappa B and mitogen-activated protein kinase pathways. In addition, NG infection provided the activation signal to the NLRP3 inflammasome that activated caspase-1 through P2X7 receptor-dependent potassium efflux, lysosomal acidification, mitochondrial dysfunction and reactive oxygen species production pathways. Furthermore, we demonstrated that NLRP3 knockdout increased phagocytosis of bacteria by macrophages and increases the bactericidal activity of macrophages against NG. These findings provide potential molecular targets for the development of anti-inflammatory drugs that could ameliorate NG-mediated inflammation.